Pemetaan Komoditas Unggulan Sub Sektor Perkebunan Di Kabupaten Aceh Selatan. - Zakiah Zakiah; Safrida Safrida; Linda Santri (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
ABSTRACT. This study aims to analyze the main commodity plantation sub sector in South Aceh District. This study uses secondary data from the years 2005-2012. Leading commodity plantation is a commodity that has a high market demand and have the ability to supply in large quantities.Analysis Location Quotient (LQ) is used to determine the base and nonbase commodity of plantation sub sector. Mapping the leading commodity in South Aceh district to aims to determine the potential of the plantation commodities which have more higher economic advantage, so that it can be developed further. Commodities which have advantages in South Aceh is nutmeg, kapok, patchouli, cinnamon and coconut. Fifth seed commodity commodities classified as affected acreage and high production exceed contributions acreage and production of the same commodities from other regions in the province of Aceh.